KONSTRUKSI SOSIAL OBAT HERBAL PASCA PANDEMI COVID-19 - Rosaliza, Mita; Hanif, Tengku Abyan; Al Malik, Mahar; Hanania, Tengku Syarifah Dzikra (Universitas Lancang Kuning, 2024)
When COVID-19 hit the world, people had reconstructed their assumptions about the importance of health. To reduce morbidity and mortality, they needed various alternative actions through various kinds of drug use, both medical drugs and traditional medicines, both during and after the pandemic. Nigella Sativa herbal medicine is one of the traditional medicine options. Nigella Sativa referred to black cumin, is among the plants that the Prophet used to make herbal medication. Prophetic Hadiths show the benefits and uses of black cumin. In Indonesia, we can find the use of Habbatussauda, which can be processed and packaged in various products. This study employs a qualitative technique in field research and a social construction approach. To learn more about the advantages of habbatussauda herbs for boosting the body's immunity, it is important to discuss this issue with social construction. People consider this herbal plant important because of its potentially active anti-inflammatory properties that can fight viral and bacterial infections both during the COVID-19 epidemic and afterwards.